2014
DOI: 10.1245/s10434-014-4038-2
|View full text |Cite
|
Sign up to set email alerts
|

A New Diagnostic Method for Rapid Detection of Lymph Node Metastases Using a One-Step Nucleic Acid Amplification (OSNA) Assay in Endometrial Cancer

Abstract: The study data demonstrated that an OSNA assay using CK19 mRNA was applicable for detecting LN metastases in EC. Combined analysis using an OSNA assay and SLNs may improve individualized treatments according to LN metastatic status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 24 publications
3
29
0
Order By: Relevance
“…CK19 is the most common diagnostic marker of LN micro-metastasis in gynecological malignant tumors (7,34,35). Our study revealed that, in the primary lesion and metastatic LNs, the positive expression rate of HPA was over 80% and no less than the rate of CK19, which supported the theory that HPA could be a promising biomarker of LN metastasis in cervical cancer.…”
Section: Discussionsupporting
confidence: 82%
“…CK19 is the most common diagnostic marker of LN micro-metastasis in gynecological malignant tumors (7,34,35). Our study revealed that, in the primary lesion and metastatic LNs, the positive expression rate of HPA was over 80% and no less than the rate of CK19, which supported the theory that HPA could be a promising biomarker of LN metastasis in cervical cancer.…”
Section: Discussionsupporting
confidence: 82%
“…Concordance of the OSNA method and the standard histopathological examination was 97.1%. 15 A detailed ultrastaging method of the processing of sentinel lymph node parts would further improve the comparison of both the methods, including the detection of phenomena comprising micrometastases, ITC or benign epithelial inclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [17, 18] have shown that the CK19 copy number for metastasis-negative LN is considerably lower than that for positive LN. In our study, all pathologically positive LN showed an obviously higher level of copy number compared with negative LN.…”
Section: Discussionmentioning
confidence: 98%
“…Nagai et al [18] reported that CK19 protein expression was observed in 98% of primary tumors. Moreover, both type 1 and type 2 tumors showed CK19 protein expression.…”
Section: Discussionmentioning
confidence: 99%